Analisis Minat Baca Peserta Didik Melalui Program Pembiasaan Literasi di Sekolah Dasar - Dian Shafrina Ilmi; Ermawati Zulikhatin Nuroh (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to describe the level of reading interest among students through the implementation of a literacy program in grade IV at SD Muhammadiyah 2 Tulangan and to examine the supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive design. The participants of this study consisted of classroom teachers, librarians, and fourth-grade students who were selected using purposive sampling. The research data were obtained through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing by applying source triangulation to ensure data validity. The results showed that the reading interest of fourth-grade students was in the moderate category. The implementation of literacy habit-forming programs, which included 15 minutes of reading before class, the use of classroom reading corners, library visits, rewards, mobile library services, and literacy competitions, contributed positively to student engagement in reading activities. Supporting factors include the implementation of a reward system, cooperation between schools and regional mobile libraries, and the implementation of literacy competitions. Meanwhile, inhibiting factors include limited time allocation for literacy activities and low intrinsic motivation among students. The research findings show that the literacy program has been implemented quite well, but it still needs to be strengthened in terms of consistency in order to increase students' interest in reading on an ongoing basis.